Correlation between body mass index (BMI) and the Gleason score of prostate biopsies in Chinese population - Zhou, Feng (Oncotarget, 2016)
We assessed the correlation between BMI and Gleason score in prostate biopsies in Chinese Population. In this retrospective study, we collected the Gleason score, PSA, BMI, age, race, and other related clinical data on 290 patients who had undergone prostatic biopsy. We then compared the prostate cancer detection rates and Gleason scores between the high BMI group (BMI ≥ 25; 143 cases) and low BMI group (< 25; 147 cases). Among the 137 patients in whom prostate cancer detected, 70 had high BMIs and 67 had normal BMIs, making the detection rates 48.95% and 45.58% respectively. Seventeen prostate cancer patients had low Gleason scores (Gleason score < 7), while 120 had high Gleason scores (≥ 7). Within the high BMI group, 44.76% had high Gleason scores, which was significantly greater than the 38.10% in the low BMI group (P = 0.027). These results indicate that while there was no effect of BMI on the rate of positive prostate cancer biopsies, the rate of high Gleason scores was greater in the high BMI group than the normal BMI group.